Poetry "Sacred Defense" in Modern Persian Literature - Akhmedova, Mastura Negmatdzonovna; Giniyatullina, Alsu Junisovna; Nigmatullina, Alsu Mansurovna (Journal of History Culture and Art Research, 2019)
The topicality of the problem under study is conditioned by the fact that, in the studies on Persian poetry, in contrast to previous eras, certain dynamics was noted, the dynamics which aimed at identifying the dominant trends in the development of Persian literature as a whole. The purpose of the article is to study the processes that led to the change of traditional views by the modernistic ideology; revealing the author's individuality. The public sentiment and the role of the poet at the contemporary stage, the assessment of the creative heritage and the fresh angle on the world, the relationship between the artist and the environment, philosophical ideas and personal experiences were in sight and received refraction in the artistic process. This article is a part of the history of Iranian literature from ancient times to the present day and can be used by various specialists (literary scholars, graduate students, students), as well as reading special courses on contemporary Iranian poetry.